The Influence of Green Attribute Communication on Electric Vehicle Purchase Intention Mediated by Green Trust - virna estriana (Jogjakarta Communication Conference (JCC), 2026)
The increasing promotion of electric vehicles as a sustainable mobility solution has encouraged automotive companies to use green attribute communication strategies to shape consumer perceptions of the product's environmental value. On the other hand, increased exposure to sustainability messages has also raised doubts about the credibility of environmental claims, thus placing consumer trust as a crucial factor in purchasing decisions. This study aims to analyze the influence of green attribute communication on electric vehicle purchase intentions with green trust as a mediating variable. Green attribute communication is represented through green brand image, green perceived quality, and green perceived value. This study used a quantitative approach with a survey method of 200 millennial respondents working in the SCBD area of Jakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that all dimensions of green attribute communication had a positive and significant effect on green trust and green purchase intention. In addition, green trust was proven to act as a mediating variable that strengthens the relationship between green attribute communication and purchase intention. These findings confirm that sustainability communication not only shapes consumer perceptions but also plays a role in building trust as a psychological mechanism that encourages sustainable consumption behavior. This research contributes to the development of green marketing and sustainability communication studies by positioning green attributes as a message construct that influences consumer perceptions and trust in the context of electric vehicles.